1996
DOI: 10.1128/mcb.16.6.2802
|View full text |Cite
|
Sign up to set email alerts
|

An Exceptionally Conserved Transcriptional Repressor, CTCF, Employs Different Combinations of Zinc Fingers To Bind Diverged Promoter Sequences of Avian and Mammalian c-myc Oncogenes

Abstract: We have isolated and analyzed human CTCF cDNA clones and show here that the ubiquitously expressed 11-zinc-finger factor CTCF is an exceptionally highly conserved protein displaying 93% identity between avian and human amino acid sequences. It binds specifically to regulatory sequences in the promoter-proximal regions of chicken, mouse, and human c-myc oncogenes. CTCF contains two transcription repressor domains transferable to a heterologous DNA binding domain. One CTCF binding site, conserved in mouse and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
558
5
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(587 citation statements)
references
References 31 publications
20
558
5
1
Order By: Relevance
“…Region V was the only other promoter region that showed an increase in the p300 and HDAC3 occupancy levels (3.3-and 9-fold, respectively). Regions IV and V contain binding sites for transcription factors MAZ (Me1a2; Izzo et al, 1999), E2F (Albert et al, 2001), CTCF (Filippova et al, 1996) that function as repressors and also TBP (TATA box; see Figure 2b). …”
Section: Resultsmentioning
confidence: 99%
“…Region V was the only other promoter region that showed an increase in the p300 and HDAC3 occupancy levels (3.3-and 9-fold, respectively). Regions IV and V contain binding sites for transcription factors MAZ (Me1a2; Izzo et al, 1999), E2F (Albert et al, 2001), CTCF (Filippova et al, 1996) that function as repressors and also TBP (TATA box; see Figure 2b). …”
Section: Resultsmentioning
confidence: 99%
“…The same protein can act as a repressor, 1 activator, 2 or insulator 3 when bound to different DNA sites. The genome-wide distribution of CTCF occupancy also suggests variation in function.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of CTCF protein expression has been detected in invasive ductal carcinoma [10], but expression levels in LCIS and infiltrating lobular carcinomas remain unknown. CTCF is a widely expressed transcription factor that is involved in different aspects of gene regulation including promoter activation [14] and repression [15], hormone-responsive gene silencing [16], methylation-dependent chromatin insulation and genomic imprinting [17,18]. It has also been shown that CTCF can inhibit cell growth and induce cell cycle arrest at multiple stages [19].…”
Section: Introductionmentioning
confidence: 99%